2012
DOI: 10.1177/0883073812460918
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Hypotonia and Brain Tumors in Children With Neurofibromatosis Type 1

Abstract: Children with the neurofibromatosis type 1 (NF1) inherited tumor predisposition syndrome are at risk for the development of brain tumors. In addition, children with neurofibromatosis type 1 often exhibit low tone (hypotonia). In this study, the authors explored the hypothesis that hypotonia could be a clinical indicator of glioma in children with neurofibromatosis type 1. A total of 56 children between 1 and 7 years of age with a confirmed diagnosis of neurofibromatosis type 1 were evaluated. Brain magnetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…The overall percentage of patients with low tone in this cohort is similar to the percentage found in a previous study. 4 The demographic characteristics of the hypotonic and normotonic groups were similar ( Table 1). All measures, with the exception of average knee range of motion and triceps fat percentage, independently displayed significant correlation with a clinical (subjective) assessment of hypotonia (Table 2).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The overall percentage of patients with low tone in this cohort is similar to the percentage found in a previous study. 4 The demographic characteristics of the hypotonic and normotonic groups were similar ( Table 1). All measures, with the exception of average knee range of motion and triceps fat percentage, independently displayed significant correlation with a clinical (subjective) assessment of hypotonia (Table 2).…”
Section: Resultsmentioning
confidence: 88%
“…In this population, previous pilot investigations have revealed that hypotonia correlates with the presence of a brain tumor. 4 However, in this study, hypotonia was diagnosed using the clinical impression of the treating physician or nurse practitioner, including resistance to passive movement of the extremities and “general global impression” of the amount of tone present. In light of this potential association between brain tumors and hypotonia in children with neurofibromatosis type 1, this patient population provides an ideal platform to formulate diagnostic criteria for hypotonia.…”
mentioning
confidence: 99%
“…After the removal of duplicates, and title and abstract screening, 35 were agreed to be reviewed full-text. Twelve articles [14,15,18,[20][21][22][23][24][41][42][43][44] reporting seven distinct studies met the inclusion criteria. In addition, two other hypotonia measurement scales were identified through citation and hand-searches.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there is no agreement on how hypotonia should be measured in children [14][15][16]. This issue has been raised in the literature through surveys [17][18][19], expert consensus studies [20], proposals [14,[21][22][23], and a clinical algorithm has been developed [24]. However, as yet, no hypotonia measurement tools that are reliable or valid for use in clinical practice have been recognized or widely implemented.…”
Section: Of 34mentioning
confidence: 99%
“…In an effort to identify features that positively or negatively correlate with specific neurofibromatosis type 1–associated symptomatology, prior investigations have attempted to identify prognostic relationships between specific features (e.g., hypotonia) and the development of more serious medical problems in this condition (e.g., optic pathway gliomas). 5 As such, one study revealed a potential association between macrocephaly and the presence of optic pathway gliomas. 6…”
mentioning
confidence: 99%